Mediation Institutions - Eishan Jan, Mohammad Naqib; Daud, Mahyuddin; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
Mediation has recently become popular alongside the other means of alternative dispute resolution (ADR) mechanisms. The interest in mediation is universal, and the rise of mediation is global. In Malaysia, mediation is still at the beginning phase, and is still not a widely-acknowledged ADR means, both in private mediation or court-based mediation. Nonetheless, efforts have been made by the judiciary as well as the Bar Council to endorse parties in disputes to choose mediation.1 The process to increase awareness for mediation has been mooted by the Malaysian government, judicial and legal fraternity, of which was realised through the passing of the Mediation Act 2012. Parties are not obliged to mediate before litigation and arbitration, which is also an attractive element for consideration. Established professional mediation institutions in Malaysia provide mediation services to the public. This includes the Financial Mediation Bureau (‘FMB’), the Malaysian Mediation Centre (‘MMC’), the Asian International Arbitration Centre (‘AIAC’) and the Legal Aid Bureau (‘LAB’). Mediation services operated by the courts are known as court-annexed mediation or judge-led mediation. Sessions are mediated by the High Court Judges, Sessions Court Judges, Magistrates and their Registrars. This chapter deliberates the background, roles, jurisdiction and relevant procedures of mediation institutions in Malaysia.